Antimicrobial resistance and antibiotic consumption in Mexican hospitals - María Guadalupe Miranda-Novales; Karen Flores-Moreno; Yolanda López-Vidal; Mauricio Rodríguez-Álvarez; Fortino Solórzano-Santos; José Luis Soto-Hernández; Samuel Ponce de León-Rosales; UNCAR Network (Salud Pública de México, 2019)
Objective. To establish the current situation of antimicrobial resistance and antibiotic consumption in Mexican hospitals. Materials and methods. Antimicrobial susceptibility data from blood and urine isolates were collected. Defined daily dose (DDD) of antibiotic consumption/100 occupied beds (OBD) was calculated. Results. Study period: 2016 and 2017. Of 4 382 blood isolates, E. coli and K. pneumoniae were most frequently reported, with antimicrobial resistance >30% for most drugs tested, only for carbapenems and amikacin resistance were <20%. A. baumannii had antimicrobial resistance >20% to all drugs. Resistance to oxacillin in S. aureus was 20%. From 12 151 urine isolates, 90% corresponded to E. coli; resistance to ciprofloxacin, cephalosporins and trimethoprim/sulfamethoxazole was >50%, with good susceptibility to nitrofurantoin, amikacin and carbapenems. Global median antimicrobial consumption was 57.2 DDD/100 OB. Conclusions. This report shows a high antimicrobial resistance level in Gram-negative bacilli and provides an insight into the seriousness of the problem of antibiotic consumption.